Courage to Create: A New Music Education Degree in Instrumental and Vocal Teaching - Ernest H. C. Lim; Rebecca Y. P. Kan; Nellie S.-R. Seng (Education Sciences, 2024)
As a special partnership that offers a unique way to strengthen the arts and cultural developments in Singapore, a new curriculum was offered to prepare students for instrumental and vocal teaching careers, with a focus on pedagogical instruction and educational theory. The purpose of this study is to explore the experiences of music-student teachers engaged in this new programme within a conservatoire context. This paper outlines the framework of a new BEd (Honours) course in Instrumental and Vocal Teaching that addresses the current problem of conservatoire students being inadequately prepared for a profession in (studio) music teaching. Data were captured through focus group interviews with the first two cohorts of this programme in 2023. Three principal themes emerged from the thematic analysis, relating to how students valued contextualization, criticality and conversations within this new curriculum. The results highlight the impact of a specialist education that allows musicians to shape their profession in instrumental and vocal teaching, debunking the notion that conservatoire education is exclusive to talented performers.